Mindfulness and Eudaimonic Well-being as Intrinsic Predictors of Extra-Role Behaviors - Nourafkan, Nadia Jobbehdar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
This dissertation examines mindfulness as a factor that leads to Organizational Citizenship Behavior (OCB) and Innovative Work Behavior (IWB) during the COVID-19 pandemic; besides how eudaimonic workplace well-being mediates these relationships. We applied Partial Least Squares Structural Equation Modeling (PLSSEM) to develop structural and measurement models also to test hypotheses. Data were collected from 255 university academics in Northern Cyprus. The results indicate that mindfulness significantly improves academics’ eudaimonic well-being and OCB, however, it does not affect their IWB directly. The relationship between mindfulness and IWB works via eudaimonic well-being as a full mediator of this relationship. Eudaimonic well-being partially mediates the mindfulness-OCB relationship as well. Findings of this study impress the significance of mindfulness and eudaimonic wellbeing for university managers to improve their academics’ OCB and IWB, as important sources of universities’ success. Additionally, results showed the prominent role of mindfulness in guaranteeing academics’ eudaimonic workplace well-being (even under extraordinary conditions such as pandemic, economic crises, war, etc.). This study is the first empirical research that considers the mediator of the relationship of mindfulness with OCB and IWB. Eudaimonic well-being sheds light on the underlying mechanism of these relationships by playing the mediator role. The novel construct of eudaimonic well-being played a mediator role for the first time in this study.

ÖZ: Bu tez, farkındalığı, COVID-19 salgını sırasında Örgütsel Vatandaşlık Davranışına (ÖVD) ve Yenilikçi İş Davranışına (YİD) yol açan bir faktör olarak incelemektedir. Ayrıca eudaimonik refahının bu ilişkilere nasıl aracılık ettiğini ele alıyor. Yapısal ve ölçüm modellerini geliştirmek ve hipotezleri test etmek için Kısmi En Küçük Kareler Yapısal Eşitlik Modellemesi (PLS-SEM) uygulanmıştır. Veriler Kuzey Kıbrıs'taki 255 üniversite akademisyeninden toplanmıştır. Sonuçlar, farkındalığın akademisyenlerin eudaimonic refahını ve ÖVD'yi önemli ölçüde geliştirdiğini ancak bunun YİD'yi doğrudan etkilemediğini göstermektedir. Farkındalık ve YİD arasındaki ilişki, bu ilişkinin tam aracısı olarak eudaimonik refahı üzerinden çalışmaktadır. Eudaimonik refahı, farkındalık-ÖVD ilişkisine de kısmen aracılık ediyor. Bu çalışmanın bulguları, üniversite yöneticileri için akademisyenleri, üniversite başarısının önemli kaynakları olarak, ÖVD ve YİD’ına teşvik etme yolunda farkındalığın ve eudaimonik odaklı işyeri refahının önemini vurgulamaktadır. Ek olarak, sonuçlar, akademisyenlerin işyerindeki eudaimonik refahını garanti etmede farkındalığın önemli rolünün gösterdi (salgın, ekonomik kriz, savaş vb. gibi olağanüstü koşullar altında bile). Bu çalışma, farkındalığın ÖVB ve YİD ile ilişkisinde aracı değişkeni ele alan ilk ampirik araştırmadır. Eudaimonik refahı, aracı rolü oynayarak bu ilişkilerin altında yatan mekanizmaya ışık tutuyor. Eudaimonik refahının yeni yapısı, ilk kez bu çalışmada aracı bir rol oynadı.
Doctor of Philosophy in Business Administration. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2023. Supervisor: Prof. Dr. Cem Tanova
Keywords: Business Administration Department; Organizational citizenship behavior; Mindfulness, organizational citizenship behavior, innovative work behavior, eudaimonic well-being, academics, COVID-19